Uso del Power Point como estrategia de aprendizaje en los estudiantes de segundo año de educación básica de la Unidad Educativa Monterrey del cantón Babahoyo provincia de Los Ríos - Briones Chuquiana, Carla Mercedes (2021)
The use of digital presentations in teaching has spread widely. To do so, it is necessary to take into account certain didactic, methodological, pedagogical and even psychological aspects that make the transfer of technology from a work area to a study area feasible. For this reason, the most salient characteristics of the PowerPoint presentations, both formal and conceptual, are reviewed, highlighting the aspects that must be taken into account for their preparation and their correct use in the classroom. The most frequent errors in their use are also indicated, indicating, in addition, how these can be overcome. Among student-centered didactic approaches, what is essential is that the student can actively create and participate. If we plan activities that have to do with discovery learning or meaningful learning, we can undoubtedly encourage our students to use digital tools as a learning strategy that involves them in environments of analysis and reflection that allow them to build their own knowledge. Through this tool, learning communities with common interests and groups with similar themes are being created. The use of technological tools in teaching implies a new conception in the capacities of the students in which not only their intellectual aptitudes are considered, but also all those that account for their integral formation. Among the most relevant aspects generated by new technologies are those related to facing the requirements and difficulties to access, handle and use information, which implies: knowing how to use the internet, knowing search strategies, access and knowing how to use the information, have the ability to synthesize and organize and systematize and finally, have the ability to assess compliance with information needs.